2022
DOI: 10.1155/2022/9228394
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Phenolic Compounds by Spectrometry and Chromatography in Lime Juices

Abstract: Juice demand has been increasing at a rapid rate in recent years, and one of the major efforts underway to meet this demand is to minimize changes during the juice process. Due to the high consumption of juice and the carcinogenicity of synthetic and chemical substances, this research uses high performance liquid chromatography (HPLC) and spectrophotometry to detect fake juices. For the detection of fraud, the tests of sodium and potassium content along with determining the amount of flavonoids (hesperidin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…In another study, hesperidin was detected in sweet lime (Citrus limetta) at a level from 29.05 to 31.67 mg/100 mL [9]. In the commercial lime juices of C. latifolia, the amount of hesperidin ranged from 2.8 to 5.6 mg/100 mL [48], much lower than the amount found in this study. Eriocitrin was the second-highest component that was quantified in lime juices.…”
Section: Flavonoids Of Lime Juicescontrasting
confidence: 79%
See 1 more Smart Citation
“…In another study, hesperidin was detected in sweet lime (Citrus limetta) at a level from 29.05 to 31.67 mg/100 mL [9]. In the commercial lime juices of C. latifolia, the amount of hesperidin ranged from 2.8 to 5.6 mg/100 mL [48], much lower than the amount found in this study. Eriocitrin was the second-highest component that was quantified in lime juices.…”
Section: Flavonoids Of Lime Juicescontrasting
confidence: 79%
“…The qualitative analysis results also revealed that the flavonoids of C. latifolia juice were more diverse compared to that of C. limonia. Hesperidin, eriocitrin, and diosmin have been extensively reported as major flavonoids of lime juice [9,47,48]. Lime juices also contain important flavonoids such as naringin and rutin [46,[49][50][51].…”
Section: Flavonoids Of Lime Juicesmentioning
confidence: 99%
“…Morever, the antioxidant effect of various phytochemicals in the medicinal plant has been reported (Dokhani et al, 2022;Falahi et al, 2019). Antioxidant activity is defined as biological property, which may preserve different foods from the toxic impacts of oxidants (Shakeri et al, 2022). The polyphenols showed antioxidant, antiproliferative activities, and apoptosis-inducing, which can be greatly effective in the prevention of various illnesses, mainly cancer (Ramos et al, 2008).…”
Section: Intorductionmentioning
confidence: 99%
“…Phenolic phytochemicals exhibit noteworthy antioxidant activity and possess particular therapeutic properties such as anti-diabetic and anti-hypertensive activity. ( Altememy et al, 2022 , Abdi-Moghadam et al, 2023b , Shakeri et al, 2022 ). One of the good sources of phenolic compounds is pepper ( Chan et al, 2018 , Zhang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%